2014
DOI: 10.1176/appi.ps.201200375
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid Lapses and Low-Income Young Adults’ Receipt of Outpatient Mental Health Care After an Inpatient Stay

Abstract: Objective This study examines low-income young adults' use of outpatient mental health services following an inpatient mental health stay, with a focus on Medicaid enrollment lapses and public mental health safety net coverage. Methods The sample included (N=1174) young adults ages 18 to 26 years who had been discharged from inpatient care in a mid-Atlantic state. All were Medicaid enrolled at the time of discharge and all were eligible for continued public mental health services regardless of Medicaid enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The transition to adulthood is especially complicated for youth leaving public social service systems, because they often face disrupted access to services as they exit child-serving systems, even though they remain in need (Osgood, Foster, Flanagan, & Ruth, 2005; Slade, Wissow, Davis, Abrams, & Dixon, 2014). Whereas some former system youth (i.e., those young adults who had access to public assistance facilities and treatment as children) who had been diagnosed with a mental illness during childhood experience a remission of symptoms in young adulthood, others experience a complicated period of unmet need (Courtney et al, 2011; Teplin, Welty, Abram, Dulcan, & Washburn, 2012).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The transition to adulthood is especially complicated for youth leaving public social service systems, because they often face disrupted access to services as they exit child-serving systems, even though they remain in need (Osgood, Foster, Flanagan, & Ruth, 2005; Slade, Wissow, Davis, Abrams, & Dixon, 2014). Whereas some former system youth (i.e., those young adults who had access to public assistance facilities and treatment as children) who had been diagnosed with a mental illness during childhood experience a remission of symptoms in young adulthood, others experience a complicated period of unmet need (Courtney et al, 2011; Teplin, Welty, Abram, Dulcan, & Washburn, 2012).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The critical period of transition out of these systems presents an opportunity for interventions to improve mental health service engagement. However, it is not clear what type of interventions are needed because service discontinuation is the product of both the individual’s choice to stop treatment (McMillen & Raghavan, 2009) and disrupted access to services (Davis, 2003; Slade et al, 2014). Little is known specifically about how former system youth perceive their symptoms and diagnoses, a potential target for intervention to increase their disposition to seek formal treatment.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Among youth with mental health disorders that fall under the "other mental disorders" category (e.g., anxiety, affective, and disruptive behavior disorders)-who make up 28 percent of all children receiving SSI after reaching age 18-more than half (53 percent) lose eligibility upon redetermination (Hemmeter, 2012). Overall, these age-based criteria contribute to higher risk of Medicaid disenrollment during young adulthood, even among highly vulnerable clinical populations (Davis et al, 2014;Pullman et al, 2010), and may contribute to reduced access to needed behavioral health care (Slade et al, 2014). Although discussed here in the context of behavioral health transitions, many of these same discontinuities apply more generally to health care coverage issues for young adults.…”
Section: Aging Out Of Child-serving Systemsmentioning
confidence: 99%
“…Even if an individual wants to get care and is fully invested in treatment engagement, they may face environmental barriers. For example, one study reported that Medicaid lapses were associated with fewer clinic visits [45]. And, studies have illustrated that lack of transportation and child care are barriers to engagement among parents of young children [6].…”
Section: Identifying the Immediate Targets For Change In Engagement Amentioning
confidence: 99%